Eksplorasi Jamur Indigenous Tanaman Jambu Bol Gondang Manis Pada Cekaman Kemarau - Nur Afifah; Ambar Susanti; Ruri Febrianti (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this study was to determine the biodiversity of indigenous fungal in the Gondang Manis Jamaican Aplle plant in Jombang Regency under drought stress. The research was carried out in July 2020. Exploration was carried out on the soil in the rhizosphere and plant tissue, which has the potential to support its resistance in dry season conditions so as to maintain the quality and quantity of Gondang Manis Jamaican Apple as a superior local plant. There were seven morphologically identified fungal species in the soil rhizosphere and plant parts of Gondang Manis Jamaican Apple in Jombang Regency during dry season stress, namely Trichoderma sp., Aspergillus sp., Penicillium sp., Fusarium sp., Beauveria sp., Mikoriza sp., and Metarhizium sp, and there was one fungus that has not been identified. The highest number of fungal species was found in the rhizosphere soil, and Trichoderma sp was the fungus found in all samples. Meanwhile, Metarhizium sp, was more commonly found in the leaves of plants. Fungal species Trichoderma sp., Aspergillus sp., Penicillium sp., Beauveria sp., Mycorrhiza sp., and Metarhizium sp. is located as a biological agent, while Fusarium sp. is included in plant pathogenic fungi